2011
DOI: 10.1111/j.1600-0765.2011.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteome data set of human gingival crevicular fluid from healthy periodontium sites by multidimensional protein separation and mass spectrometry

Abstract: Background and Objective Gingival crevicular fluid (GCF) has been of major interest for many decades as valuable body fluid that may serve as a source of biomarkers for both periodontal and systemic diseases. Because of its very small sample size, sub-μl level, identification of its protein composition by classical biochemical methods has been limited. The advent of highly sensitive mass spectrometric technology has permitted large-scale identification of protein components of many biological samples. This tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 47 publications
4
58
0
2
Order By: Relevance
“…Among many other components, blood contains serum, hemin and hemoglobin24 but the hemolytic capacity of pathobionts can also increase their concentration25. It is already described that hemoglobin and hemin have a peroxidase activity172627.…”
Section: Discussionmentioning
confidence: 99%
“…Among many other components, blood contains serum, hemin and hemoglobin24 but the hemolytic capacity of pathobionts can also increase their concentration25. It is already described that hemoglobin and hemin have a peroxidase activity172627.…”
Section: Discussionmentioning
confidence: 99%
“…In the GCF, pro-inflammatory cytokines and a vast array of other proteins can be found, especially in diseased subjects [8]. Recent reports have shown that, even in healthy periodontal microenvironment, GCF contains local proteins derived from extracellular matrix components and degradation products, as well as serum-derived proteins [7,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…This multi-biomarker approach has progressed by recent advances in clinical proteomics [1214]. Many studies have been performed in GCF analyzing its proteome profile through mass spectrometry (MS) technology [7,9,10,1519]. Those studies differed in relation to the clinical condition, including studies of experimental gingivitis [15,16], aggressive periodontitis subjects [7], CP subjects [9,18,19], and healthy subjects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for measuring only the volume of the fluid are nowadays considered insufficient and have been replaced with the composition analyses, which can identify individual proteins of inflammatory and immune responses, proteinase inhibitors, hydrolytic enzymes, intracellular proteins, construction proteins of the cytoskeleton and apoptotic and signalling proteins (6,40). Based on the above-mentioned analyses, it is possible to determine the current level of periodontal damage, and the future course of the disease can be anticipated.…”
Section: Gingival Crevicular Fluidmentioning
confidence: 99%